KETERKAITAN PERBANKAN AMERIKA TERHADAP TERJADINYA KRISIS SUBPRIME MORTGAGE - Murharsito Murharsito (Jurnal Dinamika Ekonomi & Bisnis, 2008)
AbstractThe credit crisis of 2007 started in the subprime mortgage market in the United State??s. Banks have suffered liquidity problems, concerned about the magnitude of future write downs and counterparty risk, have been trying to keep as much cash as possible as a cushion against potential losses. The severity of the crisis on bank capital has been such that United State??s. banks have had to cut dividends and call global investors, the effects of the crisis have affected the general economy. Banking system has a very significant role in the wholesale economic activity. Bank especially United State??s Bank should be involved in the subprime mortgage crisis. Is there any changes in the management especially risk management in the banking system in United State of America. This paper tries to examine the role of banking system in the subprime mortgage credit crisis. There is closed relationship between United State??s U.S. banking with sub prime mortgage crisis. The repeal of the Glass Steagall Act that forced a structural separation of commercial banking from investment banking was the causing this problem.In order to avoid this problem, United State??s banking need to promote transparation, apply prudential risk management and linked with the complexity of the investation instrument, it needed to advance the understanding and the proper regulation.Keywords : bank, subprime mortgages, role, management